2015
DOI: 10.3390/ijerph120605846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pesticide Exposure on Immunological, Hematological and Biochemical Parameters in Thai Orchid Farmers— A Cross-Sectional Study

Abstract: Various studies have found that many Thai orchid farmers used excessive amounts of pesticides without proper protective gear, but no toxicological study has been made. This cross-sectional study aimed to evaluate the immunological, hematological and biochemical statuses of these farmers. Sixty four orchid farmers and 60 controls were studied. Plasma cholinesterase activity, the percentage and absolute number of B lymphocytes (CD19+) were significantly lower in the farmers group (3966.32 ± 1165.48 U/L, 11.61 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
6
32
1
8
Order By: Relevance
“…Results from the current report regarding pesticide use and hematological parameters are consistent with previous studies which failed to reveal a consistent relationship between pesticide exposure and hematological parameters among farmers 21,27,28 . Thus, a Thai study with orchid farmers found no significant differences in hematological parameters between subjects highly exposed to pesticides and non-exposed subjects 21 .…”
Section: Pesticide Use and Hematological Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…Results from the current report regarding pesticide use and hematological parameters are consistent with previous studies which failed to reveal a consistent relationship between pesticide exposure and hematological parameters among farmers 21,27,28 . Thus, a Thai study with orchid farmers found no significant differences in hematological parameters between subjects highly exposed to pesticides and non-exposed subjects 21 .…”
Section: Pesticide Use and Hematological Parameterssupporting
confidence: 90%
“…Results from the current report regarding pesticide use and hematological parameters are consistent with previous studies which failed to reveal a consistent relationship between pesticide exposure and hematological parameters among farmers 21,27,28 . Thus, a Thai study with orchid farmers found no significant differences in hematological parameters between subjects highly exposed to pesticides and non-exposed subjects 21 . An Egyptian study only found increased leukocyte count in farmers compared to non-ex- 27 , while an Indian study observed decreased leukocytes count in pesticide-exposed workers vs. unexposed individuals but no significant differences in erythrocytes, hemoglobin, and others hematological parameters 28 .…”
Section: Pesticide Use and Hematological Parameterssupporting
confidence: 90%
See 1 more Smart Citation
“…Our suggestion is supported by the data in Table 8 which showed increased visits to different clinics due to long term exposure to pesticides. More supports come from Sarhan and Al-Sahhaf [48] and Aroonvilairat et al [49], who showed lower levels of serum proteins and increase in creatinine and blood urea and renal damage among farmers exposed to organophosphourus insecticides. Moreover, the increased number of farmer visits to hospital or private clinics indicates the progressive toxicity increase.…”
Section: Demographic and Occupational Parametersmentioning
confidence: 99%
“…Various studies on animal models exposed to specific pesticides have explored changes in hematological and biochemical parameters as possible biomarkers of pesticide exposure before adverse clinical health problems occur [24][25][26][27][28][29]. More recently, clinical studies on pesticide sprayers have focused on the immunological, hematological and biochemical statuses of these farmers [23,[67][68][69][70][71]. However, to our knowledge, there are no published reports on biomonitoring of children living in an agricultural community, where there is a high risk of exposure to the toxic effects of pesticides.…”
Section: Discussionmentioning
confidence: 99%